Editorial PPP 15(4) - Santos, Larissa; Queiroz, Isabela Saraiva de; Alvarenga Filho, José Rodrigues de; Queiroz e Melo, Maria de Fatima Aranha de; Quadros, Laura Cristina de Toledo; Moraes, Marcia; Galindo, Dolores; Monteiro, Ana Claudia Lima (Revista Pesquisas e Práticas Psicossociais, 2020)
.